A vallás és spiritualitás mint védőfaktor a kolozsvári RTZK vallástanárszakos hallgatóinak mentális egészsége szempontjából - Gabriella Márta GORBAI (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2024)
Religion and Spirituality as Protective Factors for the Mental Health of the Students at the Faculty of Reformed Theology and Music. This study focuses on certain aspects of spiritual well-being and examines how religiosity and spirituality can serve as protective factors in maintaining mental health and function as coping mechanisms. After a (non-exhaustive) review of the relevant literature on this subject, we present some practices and reflections used during group activities with the students of the Faculty of Reformed Theology at Cluj-Napoca. Ideally, the work of a religion teacher also has spiritual dimensions. It is important that the training includes reflections on religious, Christian spirituality. Reflecting on spirituality serves a dual purpose: on the one hand, it helps students view their spirituality as a resource for the protection of their mental health, and, on the other hand, it helps them recognize that the awareness and development of religious spirituality is also their professional duty, as it has a direct impact on the students entrusted to them.